A review on algebraic extensions in general relativity. Issue 5 (17th June 2021) - Hess, Peter O.
Abstract: A brief review on algebraic extensions of general relativity is presented. After a short summary of first attempts by Max Born and Albert Einstein, all possible algebraic extensions will be discussed, with the pseudo‐complex (pc) extension left as the only viable one, because it does not contain ghost solutions. Also some metric extensions are presented, such as the non‐symmetric gravitation theory and the Finsler metric. Some predictions of the pc extension are discussed, such as the structure of light emission of an accretion disk around a black hole, the redshift at the surface of a compact star as a function in the azimuthal angle, and whether there is an upper limit for the mass of a neutron star.